Heuristic play - Riddall-Leech, Sheila (Play in the EYFS., 2009)
How to encourage investigative, discovery play with babies and children aged 0-5. Heuristic Play is a form of exploratory, investigative play that builds a whole range of skills for all children from birth to five. This guide looks at four age groups from birth to five and provides practical activities for setting up heuristic play sessions. Each session comes with expert advice on: - How to set up the session for each age group - The level of adult involvement - How to plan for these activities within the EYFS - How heuristic play relates to schemas of behaviour This easy to read and practical guide is the only one of its kind and an absolute essential for anyone working in the early years.